Computational Tool for Analysis of Dosimetric Quantities - Adegbile, A. A.; Alausa, S. K.; Oluwafisoye, P. A.; Taiwo, T. K.; Ilori, A. O.; Bayode, O. P.; Adegbile, A. A. G; Akinosho, G. A. (The Nucleus, 2022)
Exposure of human to radiation is detrimental to health. It has been reported that when human body is wholly exposed to radiation, each organ of the body receives different amounts of radiation. The damage to each exposed organ depends on the amount of dose received, it is therefore necessary to analyze the amount of radiation dose that an organ of the body received when the whole body is exposed. A computational analysis tool was designed to facilitate the determination of the dosimetric quantities likeÂ equivalent and effective doses and provide an instant threat image analysis and hence provide a database where all the information inputted and generated are stored. The tool is able to determine the dose equivalent and effective dose to each organ when an amount of radioactive exposure value was input into the tool. The tool will assist the radiation safety officer in performing the task of radiation monitoring, quantification and thus assisting in protecting the workers in any organization where it is being used.